Taphonomy and paleoenvironments of Middle Triassic bone accumulations in the Lifua Member of the Manda Beds, Songea Group (Ruhuhu Basin), Tanzania. (29th November 2017) - Smith, Roger M. H.; Sidor, Christian A.; Angielczyk, Kenneth D.; Nesbitt, Sterling J.; Tabor, Neil J.
ABSTRACT: We report new data on the climate, paleoenvironments, and burial history of tetrapod fossils in the Middle Triassic Lifua Member of the Manda Beds (Songea Group) of southern Tanzania. Two bone-bearing intervals have been identified, both hosted by rubified floodplain mudrocks deposited alongside rivers that flowed from the Ruhuhu rift scarps into a series of subsiding basins under a warm, seasonally wet climate. The lower occurrence is a bonebed containing fossils of a large dicynodont ( Dolichuranus ), large cynodonts ( Cynognathus ), temnospondyls, small reptiles, and at least two archosauromorph reptiles. A chaotic melange of semiarticulated, disarticulated, and reworked bones associated with pedogenically mottled sandy siltstone is interpreted as having accumulated in a distal crevasse splay complex. The middle to upper Lifua bone accumulations are associated with floodplain pond and sheetwash deposits. Outcropping as isolated patches of strongly calcified rubified mudstones with lenses of reworked glaebule conglomerate, these accumulations contain partially articulated archosaur ( Asilisaurus, Nundasuchus ) and cynodont ( Scalenodon ) skeletons along with vertebrate coprolites and nonmarine bivalves (' Unio '). Changes in floodplain facies, faunal assemblage, and taphonomic style between lower and middle to upper Lifua strata are similar to those recorded between the middle and upper Burgersdorp Formation (subzones B to C of the Cynognathus Assemblage Zone) of the main Karoo Basin of South Africa. We propose that an increase in mean annual temperature and rainfall in southwestern Gondwana during Early to Middle Triassic times resulted in vegetated, semipermanent water bodies in the floodplain depressions that supported a relatively diverse assemblage of herbivorous dicynodont, cynodont, and early archosaur populations. Citation for this article: Smith, R. M. H., C. A. Sidor, K. D. Angielczyk, S. J. Nesbitt, and N. J. Tabor. 2018. Taphonomy and paleoenvironments of Middle Triassic bone accumulations in the Lifua Member of the Manda Beds, Songea Group (Ruhuhu Basin), Tanzania; pp. 65–79 in C. A. Sidor and S. J. Nesbitt (eds.), Vertebrate and Climatic Evolution in the Triassic Rift Basins of Tanzania and Zambia. Society of Vertebrate Paleontology Memoir 17. Journal of Vertebrate Paleontology 37(6, Supplement).